2020
DOI: 10.18027/2224-5057-2020-10-2-3
|View full text |Cite
|
Sign up to set email alerts
|

Is it necessary to add anti-angiogenic therapy to chemotherapy in patients with metastatic colorectal cancer and BRAF mutation? The systematic review and meta-analysis results

Abstract: Introduction: targeted anti‑angiogenic drugs are the integral component of systemic therapy for metastatic colorectal cancer. To date, there have been no prospective studies that would directly answer the question of the need to add anti‑ angiogenic agents to chemotherapy for BRAF‑mutated metastatic colorectal cancer. We performed a systematic review and meta‑analysis to evaluate the efficacy of adding anti‑angiogenic therapy to chemotherapy in patients with metastatic colorectal cancer harboring a mutation in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…The study confirmed poor prognosis of the CMS4 subtype (RR = 1.7, P = 0.021) and revealed that addition of cetuximab worsened patient survival for the CMS1 subtype ( P = 0.037)[ 74 ]. We could explain these results with fibroblast enrichment of the CMS1 subtype tumors, which decrease cetuximab activity due to the secretion of IL-16A and TGF-β[ 69 , 70 ]. These results might indicate low efficacy of cetuximab for the CMS1 subtype or bevacizumab high efficacy in the CALGB/SWOG 80405 study.…”
Section: Molecular Genetic Subtypes Of Colon Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…The study confirmed poor prognosis of the CMS4 subtype (RR = 1.7, P = 0.021) and revealed that addition of cetuximab worsened patient survival for the CMS1 subtype ( P = 0.037)[ 74 ]. We could explain these results with fibroblast enrichment of the CMS1 subtype tumors, which decrease cetuximab activity due to the secretion of IL-16A and TGF-β[ 69 , 70 ]. These results might indicate low efficacy of cetuximab for the CMS1 subtype or bevacizumab high efficacy in the CALGB/SWOG 80405 study.…”
Section: Molecular Genetic Subtypes Of Colon Cancermentioning
confidence: 99%
“…On the other hand, the CMS1 subtype is usually observed in right-sided tumors, which usually have BRAF gene mutations[ 61 ]. The addition of anti-angiogenic drugs in the first-line or second-line therapy significantly increases the survival of patients with BRAF mutations[ 57 , 70 ].…”
Section: Molecular Genetic Subtypes Of Colon Cancermentioning
confidence: 99%